The dynamics of element content in patients with lung cancer during radiotherapy - Dikiy, N.P.; Lyashko, Yu.V.; Medvedeva, E.P.; Borovlev, V.I.; Zabolotny, V.D.; Medvedev, D.V.; Pilipenko, N.I.; Starenky, V.P.; Suhina, E.N. (Вопросы атомной науки и техники, 2009)
Determination of the element contents in the biological samples (blood, serum of blood, hair) of patients with the diagnosis of lung cancer III degree is carried out during beam therapy. The method of PIXE excited by protons on the accelerator with energy 3 MeV has been used. During radiotherapy the difference in the element contents in hair of patients has not been detected. Trustworthy reduction of Fe, Cu, Mn, Ca, Sr, Rb etc is marked during treatment. The obtained results can be used as the additional test at carrying out adequate treatment in radiotherapy.